An Analysis of Writing Anxiety among EFL Graduate Program Students - Zumrah Magfirah Ruslan; Muhammad Tahir; Andi Anto Patak (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study aims to explore graduate student’ writing anxiety regarding the types and factors contributing to it. The researcher applied descriptive qualitative method to achieve the research objectives. The data were collected through interview and observation. The participants were ten graduate students of English Language Education Graduate Program of Universitas Negeri Makassar in the academic year of 2023/2024. The result of the study reveal that students experienced four primary types of writing anxiety, those are cognitive anxiety, somatic anxiety, avoidance behavior, and perfectionism anxiety. Furthermore, several factors contribute to writing anxiety, including linguistic difficulties, fear of negative evaluation, difficulties in organizing ideas, time pressure and deadlines, and overanalyzed. In addition, this study is only limited to qualitative method and only ten participants, it is recommended for the next researches to apply different method and study more participants.